Math
posted by Karlie .
Which expression is equivalent to the given expression?
12(x – 17)
A.
12x – 12 • 17
B.
12x – 17
C.
12x – 29
D.
12 + 12 • 17

None of those answers is correct.
12(x – 17) = 12x  204
Respond to this Question
Similar Questions

calc
What is dy/dx of y=12/12Xy^3 ???? Any idea anyone? 
math, drbob222
For this problem is it only asking for the exprssion(formula). Or do they want me to solve it. (1) A triangle has sides 3x+7,4x9,and 5x+6. Find the expression that represents its perimeter. My answer:P=a+b+c I think the question is … 
algebra2
1/3  5/6 = 1/X SOLVE 1/3  5/6 = 1/X Let's remove the denominators by multiplying by 12X 12X*(1/3)  12X*(5/6) = 12X*(1/X) Clear the fractions. 4X  10X = 12 6X=12 multipy by 1 6X=12 Divide both sides by 6 6X/6 = 12/6 X = 2 Check … 
algebra
24x^412x^3+48x^2/4x 24x^412x^3+12(1) 24x^412x^3+(12x) 2x^412x^312x check this problem for me please 
Algebra
Andrew factored the expression 20x^312x^2+8x as 4x (5x^212x^2+8x). But when Melissa applied the distributive law and multiplied out 4x (5x^212x^2+8x), she got 20x^348x^3+32x^2; thus, Andrew’s solution does not appear to check. … 
algebra
Andrew factored the expression 20x^312x^2+8x as 4x(5x^212x^2+8x). But when Melissa applied the distributive law and multiplied out 4x(5x^212x^2+8x),she got 20x^348x^3+32x^2; thus, Andrew's solution does not appear to check. Why … 
Algebra
Can someone help me with this please. Andrew factored the expression 20x^312x^2+8x as 4x(5x^212x^2+8x) but when melissa applied the distributive law and multiplied out 4x(5x^212x^2+8x)she got 20x^348x^3+32x thus Andrews solution … 
Math
you know that 8x = 5y you know that 3y=14z since 5 = (5/3)*3, 5y = (5/3)*(3y) so, 5y = (5/3)(3y) = (5/3)(14z) = (70/3)z now you have 5y, which is the same as 8x. You want 12x. since 12 = (3/2)*8, 12x = (3/2)*8x. 12x = (3/2)(8x) = (3/2)(5y) … 
Algebra. Please check my answers
Evaluate a/b+c^d for a=6,b=3,c=4 and d=5 A.42*** B.18 C.82 D.360 What is the simplified form of the expression ? 
Math
Which is equivalent to this expression 4(3x)+5(7) A. 12x + 35 B. 12x  35 C. 7x + 12 D. 7x  12 Which is equivalent to the inequality shown below?